แนวทางการส่งเสริมการสรางมูลค่าเพิ่มของผลิตภัณฑ์เครื่องใช้บนโต๊ะ อาหารเซรามิกฃองไทย Value Creation in the Thai Tableware Ceramic Products - แก้วมา, กัลยา (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2014)
บทคัดย่อ การศึกษาแนวทางการส่งเสริมการสร้างมูลค่าเพิ่มของผลิตภัณฑ์เครื่องใช้บนโต๊ะอาหารเซรามิก ของไทย โดยใช้การวิจัยเชิงสำรวจกลุ่มตัวอย่างจากพนักงานของโรงงานอุตสาหกรรมเครื่องใช้ บนโต๊ะอาหารทำด้วยเซรามิกในประเทศไทย จำนวนทั้งสิ้น 86 โรงงาน และการสัมภาษณ์เชิงลึก จากผู้ประกอบการอุตสาหกรรมเครื่องใช้บนโต๊ะอาหารทำด้วยเซรามิกในประเทศไทย พบว่า ปัจจัยที่ส่งผลต่อการสร้างมูลค่าเพิ่มของผลิตภัณฑ์เครื่องใช้บนโต๊ะอาหารเซรามิกได้แก่การสร้าง ขอบเขตตลาดใหม่, นวัตกรรมผลิตภัณฑ์, นวัตกรรมการบริหารจัดการ, กลยุทธ์การเป็นผู้นำ ทางต้นทุน, กลยุทธ์การสร้างความแตกต่าง, กลยุทธ์การจำภัดฃอบเขต และกิจกรรมหสักอย่าง มีนัยสำค้ญทางสถิติ 0.01 ส่วนแนวทางการส่งเสริมการสร้างมูลค่าเพิ่มของผลิตภัณฑ์เครื่องใช้ บนโต๊ะอาหารเซรามิกฃองไทย ดังนี้การจัดการนวัตกรรมในผลิตภัณฑ์ให้ผลิตสินค้าใหม่ที่ไม่เคย มีมาก่อน โดยมีกระบวนการกระจายแนวความคิดทั่วทั้งองค์กร และบริหารจัดการโดยให้ความ สำคัญกับการวิจัยและควบคุมคุณภาพสินค้าในกระบวนการผลิต กลยุทธ์ในการแข่งขัน เป็นผู้นำ ทางต้นทุนเพิ่อลดราคาผลิตภัณฑ์สร้างความแตกต่างโดยการผลิตงานที่เป็นนวัตกรรมของตนเอง และจำกัดขอบเขตในการสร้างทางเลือกให้ลูกค้าอย่างหลากหลาย ซึ่งกิจกรรมหลักที่ส่งผลให้ เกิดห่วงโซ่คุณค่าจากการสร้างเครีอข่ายความร่วมมือกับบริษัทต่างๆที่อยู่ในอุตสาหกรรมเซรามิก และกิจกรรมสนับสนุนให้เกิดการจัดโครงสร้างพื้นฐานขององค์กรให้สามารถทำงานได้อย่างมี ประสิทธิภาพ คำสำคัญ : การสร้างมูลค่าเพิ่ม; ผลิตภัณฑ์เครื่องใช้บนโต๊ะอาหารเซรามิก Abstract A study entitled “Value Creation in the Thai Tableware Ceramic Products” was an exploratory research project conducted with personnel from 86 Thai tableware ceramic products factories. The study also employed in - depth interviews with the entrepreneurs of Thai tableware ceramic products. The findings indicated that the factors affecting value creation of Thai tableware ceramic products included creating the scope of new markets, product innovation, management innovation, leadership in capital, creation of differences, scope limit, and main activities with statistical significance at 0.01.The guidelines for promoting the value creation of Thai tableware ceramic products were as follows: the entrepreneurs should come up with management innovation, such as products which have never been manufactured before. The relevant concepts should be distributed to the different organizations. The management should have a focus on research and how to control product quality during the manufacturing process. In regards to competition strategies, the entrepreneurs should consider leadership in capital to be able to reduce the price of products. Differences can be made by creating innovative products and offering customers a wide-range of products. The value chain can be achieved by creating a network of co-operation with other companies involved in the ceramic industry. Supporting activities should also be implemented to lay the fundamental structure for the organizations to have effective performances. Key words: Value Creation; tableware ceramic products